THE EFFECT OF USING AUDIO-PODCAST ON THE LISTENING SKILL OF SENIOR HIGH SCHOOL STUDENTS - Maulida, Nur Rahma; Talib, Ahmad; Muliati, A. (Universitas Negeri Makassar, 2022)
The objective of the research was to determine whether there was a significant effect of the use of audio podcasts on the students’ listening skills. This research was done at SMAN 4 Makassar. The population of this research was the students of SMAN 4 Makassar. The researchers used cluster random sampling to choose the sample of the research. The sample of this research was 25 students from XI IPA 3. The researchers used a quantitative technique. The instrument of this research was a listening test using audio podcasts which was administered as a pretest and post-test. Based on the result of the data analysis showed that the use of audio podcasts improved the students’ listening skills. It was shown by the mean post-test score which was higher than the pretest means score (51.76 > 63.63). The value of the t-test was more significant (0.005). Then, the researchers concluded that using audio podcast on listening skills has a significant effect on students’ listening skills.